2021
DOI: 10.1111/aos.14993
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous proteomics, a gateway to improved understanding and stratification of diverse uveitis aetiologies

Abstract: Purpose The vitreous proteome might provide an attractive gateway to discriminate between various uveitis aetiologies and gain novel insights into the underlying pathophysiological processes. Here, we investigated 180 vitreous proteins to discover novel biomarkers and broaden disease insights by comparing (1). primary vitreoretinal lymphoma ((P)VRL) versus other aetiologies, (2). sarcoid uveitis versus tuberculosis (TB)‐associated uveitis and (3). granulomatous (sarcoid and TB) uveitis versus other aetiologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…Recently, we reported that vitreous from sarcoid uveitis contained significantly higher CCL17 levels than vitreous from TB-uveitis (Schrijver et al 2021). This finding underscores immunopathobiological differences between sarcoid uveitis and TB-uveitis despite the high level of clinical similarity.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, we reported that vitreous from sarcoid uveitis contained significantly higher CCL17 levels than vitreous from TB-uveitis (Schrijver et al 2021). This finding underscores immunopathobiological differences between sarcoid uveitis and TB-uveitis despite the high level of clinical similarity.…”
mentioning
confidence: 53%
“…This finding underscores immunopathobiological differences between sarcoid uveitis and TB-uveitis despite the high level of clinical similarity. Moreover, we proposed vitreous CCL17 as a potential biomarker to discriminate sarcoid uveitis from TBuveitis (Youden's index 0.45, sensitivity 67% and specificity 78%) (Schrijver et al 2021).…”
mentioning
confidence: 99%
“…Genomic analysis of IOL is actively being pursued and has already revealed novel therapeutic targets towards the goal of personalized management of patients with IOL [ 91 , 92 , 93 ]. Ongoing proteomic analysis can identify novel diagnostic biomarkers for IOL [ 94 ]. Further advancements in this area have the potential to improve timely diagnoses of IOL, improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the diagnosis of IOL depends on intraocular biopsy, followed by a combination of cytologic evaluation, immunohistochemistry, and flow cytometry [ 16 , 17 ]. Moreover, molecular testing and proteomic analysis can identify novel diagnostic biomarkers for IOL, which have the potential to improve timely diagnoses of IOL and patient outcomes [ 18 ]. Hernández-Pons et al [ 19 ] used the IgH Rearrangements Molecular Analysis Kit and monoclonal amplification with three primer mixes (FR1-JH, FR2-JH, and FR3-JH) and diagnosed approximately 90% of all mature B-cell lymphoproliferative processes.…”
Section: Discussionmentioning
confidence: 99%